Exploring a sustainability imagination : a perspective on the integrating and visioning role of stories and symbolism in sustainability through an alternative education case study - Beyers, Christelle (Stellenbosch : Stellenbosch University, 2008)
Thesis (MPhil (Sustainable Development Planning and Management))--Stellenbosch University, 2008.